Social media communication : concepts, practices, data, law and ethics - Lipschultz, Jeremy Harris, 1958- (Routledge, Taylor & Francis Group, 2024)
"This updated fourth edition presents a wide-scale, interdisciplinary guide to social media communication. Examining platforms like Facebook, Instagram, Snapchat, TikTok, Twitter and YouTube, the book analyzes social media's use in journalism, public relations, advertising, and marketing. Lipschultz focuses on key concepts, best practices, data analyses, law and ethics - all promoting the critical thinking that is needed to use new, evolving and maturing networking tools effectively within social and mobile media spaces. Featuring historical markers and contemporary case studies, essays from some of the industry's leading social media innovators and a comprehensive glossary, this practical, multipurpose textbook gives readers the resources they will need to both evaluate and utilize current and future forms of social media communication. Updates to the fourth edition include expanded discussion of disinformation, the impact of artificial intelligence (AI), natural language chatbots, virtual and augmented reality technologies, and the COVID-19 infodemic. Social Media Communication is the perfect social media primer for students and professionals, and, with a dedicated online teaching guide, ideal for instructors, too"--